Disease-associated c-MYC downregulation in human disorders of transcriptional regulation. Issue 10 (29th November 2021) - Pallotta, Maria M; Di Nardo, Maddalena; Sarogni, Patrizia; Krantz, Ian D; Musio, Antonio
Abstract: Cornelia de Lange syndrome (CdLS) is a rare multiorgan developmental disorder caused by pathogenic variants in cohesin genes. It is a genetically and clinically heterogeneous dominant (both autosomal and X-linked) rare disease. Increasing experimental evidence indicates that CdLS is caused by a combination of factors, such as gene expression dysregulation, accumulation of cellular damage and cellular aging, which collectively contribute to the CdLS phenotype. The CdLS phenotype overlaps with a number of related diagnoses such as KBG syndrome and Rubinstein–Taybi syndrome both caused by variants in chromatin-associated factors other than cohesin. The molecular basis underlying these overlapping phenotypes is not clearly defined. Here, we found that cells from individuals with CdLS and CdLS-related diagnoses are characterized by global transcription disturbance and share common dysregulated pathways. Intriguingly, c -MYC (subsequently referred to as MYC ) is downregulated in all cell lines and represents a convergent hub lying at the center of dysregulated pathways. Subsequent treatment with estradiol restores MYC expression by modulating cohesin occupancy at its promoter region. In addition, MYC activation leads to modification in expression in hundreds of genes, which in turn reduce the oxidative stress level and genome instability. Together, these results show that MYC plays a pivotal role in the etiopathogenesis of CdLS and CdLS-related diagnoses and represents a potential therapeutic target for these conditions.